Deep vein thrombosis in a child with osteoarticular infection: A case report - Shrestha, Devendra; Limbu, H; Thapa, NB; Dhakal, AK (Journal of College of Medical Sciences-Nepal, 2014)
Acute osteoarticular infections are common in children and rarely complicated with deep vein thrombosis (DVT). This complication can cause significant morbidity and may even be fatal. Herein we report a ten year girl with deep vein thrombosis of left femoral vein who presented initially with septic arthritis of left knee and osteomyelitis of left femur. She required prolonged hospital admission and was managed with surgical debridement, antibiotics and anticoagulation. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 52-55 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9675